Development and Evaluation of Herbal Tablet Loaded with Pueraria tuberosa Water Extract with Use of Different Excipients - Tripathi, Yamini Bhusan (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of present paper is to develop the best quality of low cost tablets and with better effectiveness . Material and Methods: In this experiment we have used starch and some other excipients such as Microcrystalline cellulose, Acacia, Gellatin, Polyvinylpyrolidone and sodium Aliginate. The Water extract of plant Pueraria tuberosa belonging to the family of fabeacea. The herbal tablet of PT was made by wet granulation method. The finished products were characterized by standered method. For the determination of concentration, we have drawn the standard calibration curve of PT extract having absorption maxima at 221 nm in 0.1 N HCL solution. The drug obeyed Beer’s lamberd law in the concentration range of 10 μg/ml to 50 μg/ml and was found to be linear with r2 =0.988 and regression equation y= 0. 003x- 0.009. Result and Discussion: The parameters of pre formulation such as Angle of repose, Carr’s index and Husnner ratio showed good flow property. Tablets were evaluated by both official and non official testing, according to Indian Pharmacopoeia. After the official testing, the tablets made up by starch were not shown any significant change in properties . The friability of all formulations is less than 1%, except F0. Out of all, one of our formulation of herbal tablet mixed with 5% starch (FA) showed good release property within 1 hour in dissolution media, studied through in vitro method. Conclusion: These results concludes that starch can be proved as the better excipient for preparation of herbal tablets.